Addressing the Consequences of School Closure Due to COVID‐19 on Children's Physical and Mental Well‐Being - Hoffman, Jessica A. (World Med Health Policy, 2020)
Prolonged school closures are one of the most disruptive forces in the COVID‐19 era. School closures have upended life for children and families, and educators have been forced to determine how to provide distance learning. Schools are also an essential source of nonacademic supports in the way of health and mental health services, food assistance, obesity prevention, and intervention in cases of homelessness and maltreatment. This article focuses on the physical and emotional toll resulting from school closures and the withdrawal of nonacademic supports that students rely on. The COVID‐19 pandemic is shining a spotlight on how important schools are for meeting children's nonacademic needs. We argue that when students return to school there will be a more acute and wider‐spread need for school‐based nonacademic services and supports. Further, we expect that COVID‐19 will serve as a focusing event opening a window of opportunity for programmatic and policy change that improves nonacademic services and supports in the future.